Baroreflex sensitivity in premature infants - relation to the parameters characterizing intrauterine and postnatal condition - Hašková, Kateřina; Javorka, Michal; Czippelová, Barbora; Zibolen, Mirko; Javorka, Kamil (Physiological research, 2017)
At present, there are insufficient information about baroreflex sensitivity (BRS) and factors that determine BRS in premature newborns. The objective of this study was to determine the relationship between BRS and the characteristics that reflecting the intrauterine development (gestational age and birth weight), as well as postnatal development (postconception age and the actual weight of the child at the time of measurement). We examined 57 premature infants, who were divided into groups according to gestational age and postconception age as well as birth weight, and weight at the time of measurement. Continuous and noninvasive registration of peripheral blood pressure (BP) was performed in every child within 2-5 min under standard conditions using a Portapres (FMS) device. The results showed a close correlation of baroreflex sensitivity, heart rate and respiratory rate with gestational age, postconception age, birth weight and actual weight at the time of measurement premature newborns. An increase in the characteristics (ages and weights) resulted in increased BRS and diastolic arterial pressure (DAP), and in decreased heart and respiratory rates. Baroreflex sensitivity in the first week was in the group of very premature newborns the lowest (4.11 ms/mmHg) and in the light premature newborns was almost double (8.12 ms/mmHg). BRS increases gradually in relation to postnatal (chronological) and to postconception age as well as to birth and actual weight. The multifactor analysis of BRS identified birth weight and postconception age as the best BRS predictors. The two independent variables together explained 40 % of interindividual BRS variability.
Keywords: Humans; měření krevního tlaku; gestační stáří; Blood Pressure; porodní hmotnost; mužské pohlaví; Gestational Age; krevní tlak; baroreflex; Infant, Newborn; Birth Weight; Blood Pressure Determination; novorozenec; ženské pohlaví; Heart Rate; lidé; Infant, Premature; srdeční frekvence; Baroreflex; Male; novorozenec nedonošený; Female